(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
The shift to sustainable practices in business is illustrated by the emergence of ESG investing and the rise of green bonds as one of the major tools of financing the environmentally friendly projects. This paper looks into the ecosystem, outcomes, and policies concerning green bonds in both developed and emerging markets. With the help of a mixed-methods approach that includes case studies of the USA, Germany, India, and Brazil, the exchanges of similarities and differences relative to volume of issuance, legislative policies, investors and investment behavior, and social governance was carefully analyzed. The result is a distinction made between the developed and developing markets where the first has an established green bond ecosystem with high investor trust and clear policies, and the second is gaining momentum from international partnerships and innovative policies. The paper develops practical policy proposals on how to more efficiently shape the green bond markets in all the economies and make more effective steps towards sustainable finance.